PENGEMBANGAN LKS IPA TERPADU MENGINTEGRASIKAN LITERASI SAINTIFIK PADA MATERI GERAK DALAM KEHIDUPAN UNTUK SISWA KELAS VIII SMP - Esti Aprilia Usman; Asrizal Asrizal; Zulhendri Kamus (Universitas Negeri Padang, 2017)
In 2013 curriculum is required integrated science learning in Junior High School. Integrated learning isn’t implemented well yet. As solution of this problem is to make integrated science student worksheet by integrating the scientific literacy. The purpose of the research is to determine the validity, practicality and effectiveness of the student worksheet of integrated science by integrating scientific literacy. The type of research is Research and Development (R & D). Research design was limited testing this was before and after treatment. Instruments to collect data were expert validity sheet, practicality assessment sheet, effectiveness of the test sheet form of sheets of achievement test sheet, attitude observastion sheet, performance, and skill assessment sheet. Data analysis techniques were used in this research as follow: statistic descriptive, graph method, and correlation compare mean. Based on data analysis, there were two of research results. First, student worksheet of integrated science by integrating scientific literacy was very valid with average is 84.80. Second, implemention of integrated science student worksheet was practice acording teachers and students with average value respectively 89.46 and 90.30. In addition implementation of integrated science student worksheet by integrating scientific literacy was effective to improve students competencies including knowledge, attitude and skill competency.